Hubungan Penggunaan Alat Pelindung Diri Dengan Keluhan Penyakit Kulit Pada Nelayan Di Desa Motandoi Kabupaten Bolaang Mongondow Selatan - Hairil Akbar; Rumaf, Fachry; Tanib, Nurul Amel; Fauzan, Moh. Rizki; Asri, Abdul Malik Darmin (Health Safety Environment, 2025)
Background: The use of personal protective equipment (PPE) is an effort by workers to protect all or part of their body from workplace hazards or accidents. Factors influencing the use of PPE include human factors, such as knowledge, comfort, and availability of protective equipment. This study aims to identify the factors associated with the use of PPE among fishermen in Motandoi Village, South Bolaang Mongondow Regency. Methods: This is an analytical observational study using a cross-sectional design. The study was conducted in Motandoi Village, with a population of 80 fishermen. The sample size consists of 80 fishermen, and the sampling technique used was total sampling. Data analysis was conducted using the chi-square test. Result : The analysis revealed a statistically significant association between the use of personal protective equipment (PPE) and skin-related complaints. Specifically, the use of gloves (p = 0.003), protective clothing (p = 0.001), head protection (p = 0.045), and rubber boots (p = 0.021) was each significantly associated with a lower prevalence of skin complaints. Conclusion: There is a relationship between the use of personal protective equipment (boots, gloves, protective clothing, and head protection) and skin disease complaints among fishermen in Motandoi Village, South Bolaang Mongondow Regency.